Meaningful Participation in Legislative Drafting as a Manifestation of a Democratic Rule of Law - Nursetiawan, Eko; Ardhanariswari, Riris (Faculty of Law, Jambi University, 2022)
Public participation has a significant role in the law-making process. As a manifestation of a democratic legal state, it acts as a direct form of check and balance from the people. The problem discussed in this study are: 1) what is the urgency of meaningful participation in forming legislation as a manifestation of a democratic rule of law? and 2) what are the obstacles to meaningful participation in forming legislation as a manifestation of a democratic rule of law? The research uses the normative juridical method with a statute and case Approach. Subsequent to the decision of the Constitutional Court Number 91/PUU-XVIII/2020, public participation would be more meaningful (meaningful participation), with at least 3 (three) requirements, namely: the right to be heard; second, the right to be considered; and third, the right to be explained